Portal vein thrombosis in COVID-19 infection - Stefanie Sinz; Florian Glaser-Gallion; Thomas Steffen (Surgical Case Reports)
Abstract Background The COVID-19 pandemic has rapidly spread worldwide. As it is a novel disease, we have less experience in its possible appearances. Predominantly affecting the respiratory tract, about 20–43% patients also present with extrapulmonary manifestations such as coagulation disorders with thrombotic angiopathy. Case presentation In our institution, a patient presented to the emergency department with acute abdominal pain which was caused by portal vein thrombosis. As a COVID-19 nasopharyngeal antigen swab few days earlier was negative, we performed several tests to find out its etiology. After all tests were inconclusive and the patient suffered flu-like symptoms 2 weeks before, we repeated COVID-19 molecular testing and received a positive test result. The patient was treated symptomatically and received therapeutic anticoagulation. Conclusion A COVID-19 infection can also be present without typical pulmonary symptoms. In patients with severe abdominal pain and new diagnosed portal vein thrombosis, it is important to think of a COVID-19 infection. Also, the reliability of antigen nasopharyngeal swab should be considered critically, especially if performed wrongly. We recommended to perform molecular tests when in doubt. After the diagnosis of portal vein thrombosis, immediate anticoagulation is recommended to reduce the risk of further complications like intestinal infarction.